Assessment of a white matter reference region for 11C-UCB-J PET quantification. Issue 9 (September 2020) - Rossano, Samantha; Toyonaga, Takuya; Finnema, Sjoerd J; Naganawa, Mika; Lu, Yihuan; Nabulsi, Nabeel; Ropchan, Jim; De Bruyn, Steven; Otoul, Christian; Stockis, Armel; Nicolas, Jean-Marie; Martin, Paul; et al.
11 C-UCB-J is a positron emission tomography (PET) radioligand that has been used in humans for synaptic vesicle glycoprotein 2A (SV2A) imaging and as a potential synaptic density marker. The centrum semiovale (CS) is a proposed reference region for noninvasive quantification of 11 C-UCB-J, due to negligible concentrations of SV2A in this region in baboon brain assessed by in vitro methods. However, in displacement scans with SV2A-specific drug levetiracetam in humans, a decrease in 11 C-UCB-J concentration was observed in the CS, consistent with some degree of specific binding. The current study aims to validate the CS as a reference region by (1) optimizing CS region of interest (ROI) to minimize spill-in from gray matter with high radioactivity concentrations; (2) investigating convergence of CS ROI values using ordered subset expectation maximization (OS-EM) reconstruction, and (3) comparing baseline CS volume of distribution ( V T ) to nondisplaceable uptake in gray matter, V ND . Improving ROI definition and increasing OS-EM iterations during reconstruction decreased the difference between CS V T and V ND . However, even with these corrections, CS V T overestimated V ND by ∼35–40%. These measures showed significant correlation, suggesting that, though biased, the CS may be a useful estimate of nondisplaceable uptake, allowing for noninvasive quantification for SV2A PET.